PENGATURAN SANKSI PIDANA TERHADAP PENIKMAT KONTEN LIVE PORNOGRAFI DI MEDIA SOSIAL DALAM HUKUM POSITIF INDONESIA - Akhwal Fazri Zega; Erdianto Erdianto; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Cyber crime that has been developing lately is the Bigo Live social media application,which is an Android-based application using IOS which is currently being favored by users,especially from Indonesia. Technological developments have brought new forms ofpornography. In Law Number 44 of 2008 Concerning Pornography, that the meaning ofpornography is pictures, sketches, illustrations, photos, writing, sounds, sounds, movingimages, animations, cartoons, conversations, gestures, or other forms of messages throughvarious forms of media. communication and/or public performances, which contain obscenityor sexual exploitation that violates the norms of decency in society.This research is a normative legal research. This is based on library research whichtakes quotes from reading books or supporting books related to the problem under study.This study uses secondary data sources consisting of primary, secondary, and tertiary legalmaterials. This study also used qualitative data analysis and produced descriptive data.From the results of the research and discussion conducted, it is necessary to reformthe law regarding sanctions against connoisseurs of live pornographic content who carry outpornographic transactions so that it becomes a permanent job for perpetrators of livepornographic content. So that the level of criminal acts of pornography in Indonesia can bereduced. The imposition of sanctions on connoisseurs of live pornographic content is equatedwith the perpetrators of live pornographic content so that there is no difference between thetwo because they both commit criminal acts (pornographic transactions) and advise the stateto improve moral and character education for all generations of the nation about theimportance of moral values and avoidance the younger generation of pornographic contentthat is rife on social media.Keywords: Sanctions; Criminal; Content Connoisseurs; Live Pornography.